JPPIPA (Jurnal Penelitian Pendidikan IPA): Issue Information Vol 10 No 2 December 2025 (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
JPPIPA (Jurnal Penelitian Pendidikan IPA) Volume 10, Number 2 (December 2025) presents a collection of empirical studies that address current developments and challenges in science education across elementary, junior high, and senior high school levels. The articles in this issue highlight the growing emphasis on innovative instructional media, the integration of digital and emerging technologies, and learning strategies aimed at improving students’ motivation, participation, and higher-order thinking skills in science classrooms. Several studies focus on the development and evaluation of learning media designed to support conceptual understanding and student engagement, including comics-based learning media for motion and force, interactive PowerPoint integrated with augmented reality for the Solar System topic, and interactive physics e-modules developed to foster higher-order thinking skills and self-regulated learning among senior high school students. The role of technology in enhancing science instruction is further explored through research examining the use of artificial intelligence in magnetic electricity courses and the effectiveness of STEM Project-Based Learning modules in increasing student participation in physics topics such as work, energy, and simple machines. In addition to instructional innovation, this issue emphasizes student-centered and contextual approaches to learning. Studies on science learning motivation among junior high school students and the application of the Numbered Heads Together cooperative learning model in elementary classrooms provide insights into collaborative practices that encourage active learning and meaningful interaction. Furthermore, a case study assessing high school students’ environmental knowledge of mangroves and their role in climate change mitigation underscores the importance of connecting science learning with local environmental contexts and real-world issues. Overall, the articles in this volume offer research-based evidence and practical perspectives that contribute to the continuous improvement of science teaching and learning and are expected to serve as valuable references for educators, researchers, and policymakers committed to strengthening the quality, relevance, and sustainability of science education in diverse educational settings.